Degree of Approximation by Hybrid Operators - Naokant Deo; Hee Sun Jung; Ryozi Sakai (Abstract and Applied Analysis)
We consider hybrid (Szász-beta) operators, which are a general sequence of integral type operators including beta function, and we give the degree of approximation by these Szász-beta-Durrmeyer operators.